2013
DOI: 10.3109/19401736.2012.760075
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome ofLiobagrus kingi(Teleostei, Siluriformes: Amblycipitidae)

Abstract: Liobagrus kingi is endemic to southwest China and listed as endangered species (IUCN 2012). Genetic diversity is necessary for conservation issue. In studying this, the complete mitochondrial genome sequence of L. kingi has been obtained with PCR, which contains 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a non-coding control region with the total length of 16,483 bp. The gene arrangement and composition are similar to that of other vertebrates. Most of the genes are encoded on heavy strand, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We compared the results from the present study to previous mitogenome research on the genus Liobagrus (Kartavtsev et al 2007;Jia et al 2013aJia et al , 2013bJia et al , 2013cHuang et al 2017). Phylogenetic analysis based on the mitogenome sequences using the maximum likelihood approach showed that the L. mediadiposalis was closely related to Liobagrus reinii (Figure 1).…”
Section: Introductionmentioning
confidence: 62%
“…We compared the results from the present study to previous mitogenome research on the genus Liobagrus (Kartavtsev et al 2007;Jia et al 2013aJia et al , 2013bJia et al , 2013cHuang et al 2017). Phylogenetic analysis based on the mitogenome sequences using the maximum likelihood approach showed that the L. mediadiposalis was closely related to Liobagrus reinii (Figure 1).…”
Section: Introductionmentioning
confidence: 62%
“…The DNA sequence was annotated in comparison with the mitogenome of L. kingi (Jia et al 2013a) and L. nigricauda (Jia et al 2013b). Twentyone primer pairs were used to amplify contiguous, overlapping segments and to obtain the complete mitochondrial genomes of L. marginatoides with polymerase chain reaction (PCR) method.…”
mentioning
confidence: 99%